Strategy Analysis in the Management and Development of the Al Azqia Shop Business - Maymanah, Siti; Soedarsa, Herry G (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Al Azqia Shop is a store engaged in the field of building materials located in Pekon Suka Banjar, Gunung Alip District, Tanggamus Regency. It is categorized as a developing and growing business, but it still faces several challenges in operational and marketing aspects. Currently, the shop relies on manual systems to manage transactions, inventory, and customer data, which often leads to inefficiencies in service, data accuracy, and record-keeping. Furthermore, Al Azqia Shop has not yet utilized digital marketing tools or social media platforms such as Instagram, Facebook, and WhatsApp Business to promote its products, which limits its visibility and sales potential. To achieve business growth and long-term sustainability, Al Azqia Shop must adopt innovative marketing strategies that integrate digital technology and online media. The use of social media campaigns, online advertisements, and digital catalogs can help the shop reach a broader market and increase engagement with customers. Building a strong brand identity and improving customer relations through loyalty programs, responsive service, and after-sales support are also crucial in strengthening consumer trust. Additionally, implementing a marketing strategy that emphasizes competitive pricing, product quality, and convenience will enhance customer satisfaction and loyalty. By monitoring market trends and understanding customer preferences, the shop can offer promotional packages and discounts to stimulate purchasing interest. Strengthening cooperation with suppliers and adopting a semi-digital inventory management system can further improve efficiency. Through these combined efforts, Al Azqia Shop can compete effectively with other building material stores, attract more customers, and achieve sustainable business growth.